Peningkatan Pengetahuan Masyarakat Desa Penembang Kecamatan Merigi Kelindang Kabupaten Bengkulu Tengah Tentang Manajemen Pembuangan Sampah Yang Baik - Yusnita, Yuli; Ditasman, Ditasman; Eka Putra, M Bima; Al Hidayat, Rahmat; Novrianda, Herry (Jurnal Semarak Mengabdi, 2024)
One of the environmental problems that is often encountered in daily life is waste. Waste is a never-ending problem because its volume continues to increase along with population growth. The volume of waste produced by households is the second largest after industrial waste. In our daily lives we can never be separated from what is called rubbish. The problem of waste is not a new problem, because until now the waste problem has not been resolved properly, so its management needs to be carried out comprehensively and integrated from upstream to downstream in order to provide economic benefits, be healthy for the community, and be safe for the environment. In order to help the community understand how to manage waste properly, this community service aims to provide knowledge to the community or residents in Penembang village regarding the meaning of waste, characteristics of waste, waste management, good waste management planning.